The Role of Biofertilizers and Sprouted Barley Grain Extract in Enhancing the Active Compound Content of Arugula Eruca vesicaria Mill Seeds Oil to Achieve Agricultural Sustainability - Hawraa H. Al-Jibawi; Abbas K. Mijwel (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Arugula contains compounds with therapeutic and preventive roles against many diseases, and it promotes overall health. Additionally, its seeds contain promising medicinal oil that general health and disease prevention. An experiment was conducted over two agricultural seasons (autumn 2023-2024 and spring 2024) using a Randomized Complete Block Design (RCBD) with a split-plot system in three replicates to enhance the quantity and quality of the oil in the seeds. The biostimulant treatments (A) were applied to the main plots, with A1 as the control (no addition), A2 treated with Trichoderma harzianum, and A3 treated with Bacillus subtilis. Amino acids (B) were organized within the sub-plots, including B1 as the control (water spray), B2 with Arginine 150 mg L-1, B3 with Tryptophan 150 mg L-1, and B4 with Phenylalanine 150 mg L-1. The treatment with sprouted barley seed extract (C) was applied in the sub-sub-plots, with C1 as the control, and C2 involved spraying the sprouted barley seed extract at a concentration of 100 g L-1. The results showed a positive and significant effect of the biostimulant treatments Trichoderma harzianum, Bacillus subtilis, amino acids Arginine, and Tryptophan, Phenylalanine, and sprouted barley seed extract, and their interactions, in increasing the concentrations of fatty acids in arugula seed oil, including Erucic, Palmitic, Stearic, Oleic, Lenolic, and Linolenic acids. This encourages the trend towards sustainable agriculture to enhance the health value of the oil while preserving the environment and the ecosystem.